Trazodone : pharmacological and clinical profile - Decina, Paolo (UTET S.p.A. Divisione Periodici Scientifici, 2001)
The study focuses on the pharmacological profile of trazodone.
Keywords: hodnocení léčiv; Trazodone; trazodon; Drug Evaluation; farmacie a farmakologie